Delivering Bad News in Amyotrophic Lateral Sclerosis: Proposal of Specific Technique ALS ALLOW. Issue 6 (December 2021) - Edwards, Wesleigh F.; Malik, Sahana; Peters, Jonathan; Chippendale, Ivy; Ravits, John
Abstract : Purpose of Review: Physician communication skills are a critical part of care for amyotrophic lateral sclerosis (ALS) patients and caregivers. They shape the development of autonomy and quality of life, and they mitigate emotional trauma. Communication skills are especially critical at 2 different time points in the course of the disease: early when delivering and establishing the diagnosis, and later when clarifying goals of care. Recent Findings: Several techniques for physician communication of difficult information are available, including SPIKES (Setting up the interview, assessing the patient's Perception, obtaining the patient's Invitation, giving Knowledge and information to the patient, addressing the patient's Emotions with Empathetic responses, and Strategy and Summary), ABCDE (Advance preparation, Build a therapeutic environment/relationship, Communicate well, Deal with patient and family reactions, Encourage and validate emotions), and BREAKS (Background, Rapport, Exploring, Announce, Kindling, Summarize). These emphasize the physician's accountability and responsibility for communicating effectively. Formal training in these techniques is limited, and their applicability specifically to ALS is inexact. Summary: We propose an ALS-specific technique which we call ALS ALLOW to guide physicians in conducting difficult communications with ALS patients and caregivers to develop their understanding, establish autonomy, set goals, and mitigate emotional trauma. The techniques are useful in discussions both early and late stages in the disease.